PENGARUH PENGGUNAAN MEDIA GAME TWISTER MATERI SISTEM REPRODUKSI TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI MA DDI GALLA RAYA KABUPATEN PANGKEP - Qamria, Qamria; Ibrahim, Misykat Malik; Ali, Ahmad (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2025)
This study examined the effect of Twister game-based learning media on students’ learning outcomes in the reproductive system topic among eleventh-grade students at MA DDI Galla Raya, Pangkep Regency. It also compared the learning outcomes of students who used the media with those who received instruction without it. The study employed a quasi-experimental method with a non-equivalent control group design. The population consisted of 70 eleventh-grade students, from which two classes were selected through purposive sampling. Class XI MIA 1 was assigned as the experimental group, while Class XI MIA 2 served as the control group, with each group consisting of 35 students. Data were collected through pretests and posttests and analyzed using descriptive and inferential statistics to examine improvements in learning outcomes and determine whether a significant difference existed between the two groups. The findings showed that the experimental group’s mean score increased from 47.57 on the pretest to 76.14 on the posttest. In comparison, the control group’s mean score increased from 44.71 to 67.57. Hypothesis testing at a significance level of 0.05 revealed that the p-value was lower than α (0.000 < 0.05). Therefore, the use of Twister game-based learning media had a significant effect on improving students’ learning outcomes.